Socially Responsible Human Resource Management: SLR - Indri Safitri; Sopiah Sopiah (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this SLR is to analyze Socially Responsible Human Resource Management using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method with data obtained from Diva Portal, Sciencedirect, and Google Scohlar (2018-2023). After utilizing the inclusion and exclusion criteria, 36 journals were reviewed from a total of 304 journals. The findings of this study show that socially responsible HR in the workplace will benefit the surrounding environment and the company. To maintain a positive work environment, corporate responsibility for employee well-being is considered important. Providing facilities to employees, welfare programs, a safe and healthy work environment, as well as career development support is the implementation of Corporate Social Responsibility (CSR), where companies are responsible both socially and environmentally. It is a way to protect the environment, contribute to the company, and consider social, cultural, and economic considerations when running a business.